2011
DOI: 10.1161/circep.110.960419
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Ventricular Fibrillation Waveform to Predict a Return of Spontaneous Circulation and Distinguish Acute From Post Myocardial Infarction or Normal Swine in Ventricular Fibrillation Cardiac Arrest

Abstract: Background-In cardiac arrest, the ventricular fibrillation (VF) waveform, particularly amplitude spectral area (AMSA) and slope, predicts the return of spontaneous circulation (ROSC), but it is unknown whether the predictive utility differs in an acute myocardial infarction (MI), prior MI, or normal myocardium and if the waveform can distinguish the underlying myocardial state. We hypothesized that in a swine model of VF cardiac arrest, AMSA and slope predict ROSC after a shock independent of substrate and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…12 Indeed, evidence exists for ventricular fibrillation (VF) waveform changes over time, which might enable prediction of the success of a defibrillation attempt. 4,[12][13][14][15][16][17] Small clinical studies have demonstrated that amplitude spectrum area (AMSA) is one of the most accurate predictors of defibrillation success. 16,17 However, none of these studies reported any patients'…”
mentioning
confidence: 99%
“…12 Indeed, evidence exists for ventricular fibrillation (VF) waveform changes over time, which might enable prediction of the success of a defibrillation attempt. 4,[12][13][14][15][16][17] Small clinical studies have demonstrated that amplitude spectrum area (AMSA) is one of the most accurate predictors of defibrillation success. 16,17 However, none of these studies reported any patients'…”
mentioning
confidence: 99%
“…In addition, it was observed that the number of activation wave fronts was smaller than in controls, both over the infarcted and over the normal tissue of the dogs with a previous MI 17 . In the presence of an acute MI, differences in VF waveform characteristics as compared with controls may even become more apparent 10,19,20 .…”
Section: Animal Studiesmentioning
confidence: 99%
“…The primary purpose of this investigation was to determine whether the VF waveform, as measured by AMSA, can predict resuscitation outcome independent of CC quality, since chest compressions are known to raise AMSA 15,16,17,18,19 . We find that the waveform parameter AMSA-avg was a very strong and independent predictor of both hospital discharge and good neurological outcome, with survival clustered at higher values of AMSA-avg (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that AMSA rises with well-performed chest compressions in both animal 15,16,17 and human studies 18,19 . This raises the question whether it is solely chest compression quality that predicts outcome or whether the VF waveform can add independent predictive value.…”
Section: Introductionmentioning
confidence: 99%